Broodstock management of the arrow crab Stenorhynchus seticornis and effects of temperature and salinity on larvae survival - Antunes, Mariana [UNESP]; de Paiva Barros-Alves, Samara [UNESP]; Alves, Douglas Fernandes Rodrigues [UNESP]; Gregati, Rafael Augusto [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Springer Nature, 2023)
Was tested the viability of a rearing system for management of broodstock of crabs and the salinity and temperature effect in larval survival and duration of the larval stages of Stenorhynchus seticornis. We used a completely randomized 4 × 4 factorial experiment with 16 treatments and 3 replicates per treatment. Factor one was temperature with the following factor levels: 23 °C, 25 °C, 27 °C, and 29 °C and factor two was salinity: 25, 30, 35, and 40 PSU. A total of 960 larvae (zoea I), obtained from 7 females kept in the rearing system, were transferred and distributed in batches of 20 larvae kept in glass flasks (500 mL) and then subjected to temperature and salinity experiments. They were checked daily for seedlings or deaths. The larval development took from 22 to 25 days (7.3 ± 4.14), and occurred only in experimental conditions of 23 °C x 35 PSU, in which 6.6% of larvae reached the juvenile stage. About the the viability of a rearing system, 15 ovigerous females were maintained in the rearing system, composed by 6 aquaria with water-recirculation and filtering system (400 L), released from 1 to 4 viable larval lots each during 2 months. Such results highlight the importance of studies in larval interaction with environmental conditions regarding larval survival, enabling the juvenile offer for commercial purposes and restocking of native populations, also promoting a efficient system for broodstock maintenance and larval attainment for aquaculture.
Keywords: Aquaculture; Crabs; Development; Stages